(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: (1) To describe clinical and X-ray findings of teeth with apical peridontitis at the Hanoi Central Odonto-Stomatology Hospital in 2022. (2) To evaluate the results of single-visit endodontic treatment for teeth of first objective. Subjects and Methodology: An uncontrolled clinical trial research on 50 patients and 77 teeth diagnosed with acute and chronic apical periodontitis and had not received any endodontic treatment. Results: 92% of patients did not have postoperative pain. The healing rate is 78.05%, healing is 21.95%, and there are no cases of non-healed. The phenotype of S0R0D0 is 78.05%, corresponding to the healed rate. There was no case of treatment complications reported during treatment. Conclusion: Single-visit endodontic treatment for teeth with acute and chronic apical periodontitis provides a high healing rate. In addition, finishing treatment in one appointment reduces the incidence of postoperative pain.